Kajian Pustaka Hubungan Pola Konsumsi Lemak Dan Status Obesitas Sentral Dengan Profil Lipid Pasien Penyakit Jantung Koroner - Ni Kadek Widya Pratiwi; Ni Komang Wiardani; Pande Putu Sri Sugiani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Coronary heart disease is a cardiovascular disease which is a disease which is the main cause of death in developed and developing countries. Coronary heart disease occurs due to narrowing of the coronary arteries which causes obstruction of blood flow to the heart and is characterized by abnormal lipid profile levels. Some factors that cause abnormal lipid profile levels are high fat consumption besides high fat consumption will cause fat accumulation in the abdominal abnormality thus causing central obesity. The purpose of this study was to analyze the relationship between fat consumption patterns and central obesity status with lipid profiles in patients with coronary heart disease. This research is a qualitative study with a literature review research design. The subjects in this study were sufferers of coronary heart disease. Data on fat consumption patterns, central obesity status, and lpid profiles were obtained from a collection of articles with keywords: fat consumption patterns, central obesity, lipid profiles and coronary heart disease which were then tabulated and analyzed. Data were analyzed descriptively. The pattern of fat consumption in patients with coronary heart disease that is high fat consumption, with the level of consumption that is not good and frequent fat consumption that is 4-5 times a week, most patients with coronary heart disease experience central obesity, with some having LDL lipid profile levels high and low HDL. Based on the results of the analysis, it is known that there is no relationship between fat consumption patterns with lipid profiles and central obesity status with lipid profiles in patients with coronary heart disease.Keywords: fat consumption patterns, central obesity status, lipid profile, coronary heart disease.